Time to onset of bisphosphonate‐related osteonecrosis of the jaws: a multicentre retrospective cohort study. (6th March 2017) - Fung, PPL; Bedogni, G; Bedogni, A; Petrie, A; Porter, S; Campisi, G; Bagan, J; Fusco, V; Saia, G; Acham, S; Musto, P; Petrucci, MT; et al.
Abstract : Objectives: Osteonecrosis of the jaw (ONJ) is a potentially severe adverse effect of bisphosphonates (BP). Although the risk of ONJ increases with increasing duration of BP treatment, there are currently no reliable estimates of the ONJ time to onset (TTO). The objective of this study was to estimate the TTO and associated risk factors in BP‐treated patients. Subjects and Methods: Retrospective analysis of data from 22 secondary care centres in seven countries relevant to 349 patients who developed BP‐related ONJ between 2004 and 2012. Results: The median (95%CI) TTO was 6.0 years in patients treated with alendronate ( n  =   88) and 2.2 years in those treated with zoledronate ( n  =   218). Multivariable Cox regression showed that dentoalveolar surgery was inversely associated, and the use of antiangiogenics directly associated, with the TTO in patients with cancer treated with zoledronate. Conclusions: The incidence of ONJ increases with the duration of BP therapy, with notable differences observed with respect to BP type and potency, route of administration and underlying disease. When data are stratified by BP type, a time of 6.0 and 2.2 years of oral alendronate and intravenous zoledronate therapy, respectively, is required for 50% of patients to develop ONJ. After stratification by disease, a time of 5.3 and 2.2 years of BP therapy is required for 50% of patients with osteoporosis and cancer, respectively, to develop ONJ. These findings have significant implications for the design of future clinical studies and the development of risk‐reduction strategies aimed at either assessing or modulating the risk of ONJ associated with BP.